Promoting Collaborative Pedagogy in Classrooms: Challenges and Solutions - Bunmi Isaiah Omodan (STKIP Singkawang, 2021)
Collaborative pedagogy appears to be productive among students and thereby adopted in many classrooms to ensure that students are active participants in the knowledge production process. However, challenges exist among students, alongside their instructors, which hinders the active involvement of students in the collaborative knowledge production process. In the same vein, the study also examines the possible ways to navigate the challenges. The argument is located within social constructivism and conceptual analysis of collaborative pedagogy to explore the trajectories of collaborative classrooms in schools. In response to the challenges, the study proposed solutions that include promotion of unity in diversities among students, the introduction of cultural variations in classrooms, and instigation of student’s readiness to interact. The study concludes that collaborative knowledge construction is worthy of being promoted with the recommendation that schools should ensure that students are taught to be united in the process of generating knowledge and that there must be concerted efforts to teach different cultures in the system with student motivation for natural interest.